La justice est indivisible : la Palestine comme enjeu féministe - Elia, Nada (Revue PréfiX, 2024)
L’article traduit ici en français s’inscrit précisément dans cette démarche d’interpellation critique des féministes non-palestiniennes, y compris juives et racisées. Le titre « Justice is indivisible » reprend une déclaration de Martin Luther King Jr., et le sous-titre, « Palestine as a feminist issue », est inspiré d’un texte d’Angela Davis. Le texte est paru en 2017 dans un numéro spécial intitulé « Palestine Lives » de la revue aujourd’hui en dormance, Declonization : Indigenity, Education & Society, qui proposait aussi des articles comparant l’apartheid sud-africain et israélien (Leigh-Ann Naidoo) ou le colonialisme de peuplement aux États-Unis et en Israël (Johanna Fernandez). La traduction de ce texte est une initiative du Chantier sur l’antiféminisme du Réseau québécois en études féministes (RéQEF). En termes politiques, il y a alors une dizaine d’années que la bande de Gaza, minuscule territoire où s’entasse une population pauvre, y compris dans des camps de réfugié·es, est sous le contrôle du Hamas. Cette force politique islamiste en a expulsé de manière plutôt brutale le parti laïque du Fatha, du président palestinien Mahmoud Abbas qui contrôle encore aujourd’hui la Cisjordanie, menacée par les attaques de colons. En Occident, le Hamas est souvent diabolisé par la majorité comme l’équivalent palestinien de l’État islamique en Irak et en Syrie ou des talibans afghans, une force autoritaire, voire totalitaire, réactionnaire et patriarcale. Rappelons pour mémoire que bien des féministes aux États-Unis ont appuyé l’invasion militaire de l’Afghanistan par la coalition menée par les États-Unis, en 2001, tant elles espéraient voir les talibans vaincus, pour libérer les Afghanes. Pour leur part, bien des Afghanes rappelaient que leur problème principal restait la désolation que leur apportaient la guerre et la violence de l’occupation militaire occidentale, des propos qui font échos à ceux de Nada Elia au sujet de la Palestine écrasée par l’armée israélienne. Ce texte est aussi une réaction à la période 2015-2016, marquée par un regain de tensions meurtrières entre Israël et la Palestine, y compris quelques attaques aux couteaux menées par des Palestiniens à Jérusalem, qui ont attirées l’attention sur la scène internationale. En termes de rapports de force et de capacités de lutte, ces attaques aux couteaux doivent pourtant être comparées à la puissance de feu de l’armée israélienne, et même de colons, qui provoque évidemment bien plus de morts et blessés du côté palestinien qu’Israélien. L’armée israélienne, par exemple, compte 10 fois plus de chars d’assaut que l’armée française et 20 fois plus que l’armée canadienne. Le Hamas n’a pas de chars d’assaut… La publication de cette version française a été en grande partie motivée par la turbulence provoquée par l’offensive des troupes du Hamas lancée le 7 octobre qui a provoqué plus de 1 000 victimes du côté israélien, et surtout la réplique israélienne qui, à ce jour, a provoqué plus de 30 000 victimes du côté de Gaza, ainsi qu’un déplacement de plus de la moitié de la population et la destruction d’une ampleur inégalée, y compris d’hôpitaux, d’universités, d’écoles et de bibliothèques (sans parler des morts qui s’accumulent aussi en Cisjordanie). Cette violence à grande échelle a provoqué des ondes de choc dans les réseaux universitaires, y compris féministes, en Amérique du Nord et en Europe, alors que des voix (pro)palestiniennes ont été muselées par les directions d’établissement (voir, à ce sujet, Francis Dupuis-Déri, « Où sont les défenseurs de la liberté universitaire ? », Le Devoir, 25 janvier 2024). Même si le texte de Nada Elia est plutôt pessimisme à ce sujet, et traduit un terrible isolement politique, notons que quelques féministes juives se mobilisent aujourd’hui contre le génocide, dont la célèbre Judith Butler, qui réclame publiquement un cessez-le-feu, le droit de retour pour la population palestinienne et le démantèlement des structures coloniales, ainsi que Rosalind Pollack Petchesky, 81 ans, qui avait étudié l’antiféminisme et la nouvelle droit dans les années 1980, qui a codirigé en 2021 avec Esther Farmer et Sarah Sills l’ouvrage A Land With A People : Palestinians and Jews Confront Zionism et qui a été récemment arrêtée à deux reprises à New York dans des mobilisations du groupe Jewish Voice for Peace contre le gouvernement israélien et l’appui qui lui offre le gouvernement des États-Unis. Pendant ce temps, le Palestinian Feminist Collective appelle pour le 8 mars à participer à la campagne Third World Women Resist, à Chicago, Détroit, Los Angeles et San Francisco, déclarant qu’on « constate que des “féministes” sionistes, colonialistes et impérialistes s’approprient le vocabulaire des droits des femmes pour discréditer la lutte de libération palestinienne » et qu’« il n’y a pas de place pour des génocidaires et leurs alliées dans des mouvements féministes anti-impérialistes et décoloniaux. »
Keywords: approches et analyses; asie; discipline; droits des femmes*; féminisme décolonial; génocide; impérialisme; intersectionnalité; palestine; préFiX; régions géographiques; système colonial; systèmes d'oppressions; thématiques; traduction; violences

Palestine: un féminisme de libération - Elia, Nada; Hammar, Liza; Dupuis-Déri, Francis (Les éditions du remue-ménage, 2024)
"Comment expliquer qu’Israël, malgré ses attaques meurtrières à Gaza et sa violation du droit international, reste à l’abri de toute véritable critique? Pourquoi de nombreuses féministes du Nord global, si promptes à dénoncer l’impact du «fondamentalisme islamique» sur les femmes palestiniennes, restent-elles silencieuses quand il s’agit de décrier l’occupation et le génocide que perpétue l’État israélien en Palestine? En déconstruisant les associations fallacieuses entre antisionisme et antisémitisme, la professeure et militante palestinienne Nada Elia, qui vit aujourd’hui aux États-Unis, rappelle la place des femmes et des personnes queers dans la lutte pour la libération de la Palestine, et revendique le démantèlement des structures coloniales qui écrasent la population à Gaza et en Cisjordanie."– Site de l'éditeur.
Section: 124 pages, 1 page non numérotée ; 14 cm.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; antisionisme; antisémitisme; approches et analyses; asie; cours; discipline; disicpline; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; militance; palestine; pol4212; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Une nouvelle subjectivité féminine en Iran - Khosrokhavar, Farhad (Esprit, 2023)
Les jeunes générations, notamment de femmes, rejettent un régime théocratique macabre au nom de la joie de vivre et de la liberté.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; résistance; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Femmes et genre en Irak - Ali, Zahra; Ghosn, Nada (Éditions Syllepse, 2022)
"Les nombreuses questions sociologiques soulevées par Zahra Ali sur les femmes, le genre et le féminisme en Irak ont trouvé des réponses à travers son expérience quotidienne dans le pays, de 2010 à 2019, ce dont elle rend compte avec virtuosité et profondeur dans son livre. Virtuosité, car pour une journée de travail de terrain à Bagdad, il lui fallait passer une douzaine de checkpoints pour aller de la maison familiale au centre-ville. Profondeur, car ses observations ethnographiques nous permettent de comprendre comment un des pays les plus avancés de la région en termes d'éducation, de santé, d'emploi et de droits juridiques des femmes a pu devenir ce territoire militarisé contrôlé par des hommes armés, fragmenté, si difficilement vivable pour ses habitants, et encore plus pour les femmes. Son étude, mêlant ethnographie et histoire sociale, politique et orale, nous offre une compréhension des expériences sociales, économiques, politiques et féministes des femmes irakiennes. Le regard de Zahra Ali postule que les femmes, les questions de genre et les luttes féministes en Irak doivent être analysées au moyen d'un prisme complexe, relationnel et historique, sans avoir recours à l'argument d'une « culture » ou d'un « islam » indifférenciés afin d'expliquer des réalités sociales, économiques et politiques. Cet ouvrage traite autant des femmes, du genre et du féminisme en Irak qu'il est un ouvrage féministe sur l'Irak. Il contribue aux débats féministes et propose une analyse féministe postcoloniale et transnationale de l'histoire socio-politique contemporaine de l'Irak."– Quatrième de couverture.
Section: 382 pages : illustrations, plans, cartes ; 21 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme décolonial; féminisme islamique; histoire et politique; irak; premier cycle; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Invisible work at work and the reproduction of gendered social service organizations - Lavee, Einat; Kaplan, Amit (Gender, Work and Organization, 2022)
Des études démontrent que la convergence du néolibéralisme et des impératifs de la nouvelle gestion publique crée des conditions dans lesquelles les prestataires de services sociaux entreprennent divers types de travail non rémunéré, réaffirmant le rôle du genre dans la prestation de services. En s’appuyant sur ces arguments, cette étude explore le processus par lequel les pratiques non rémunérées restructurent le genre dans les organisations de services sociaux, en utilisant le concept de « travail invisible ». En appliquant la méthode d’enquête de l’ethnographie institutionnelle, nous examinons les expériences des travailleurs des services sociaux dans le secteur public israélien et opérationnalisons le travail non rémunéré comme des ressources personnelles informelles que les travailleurs fournissent aux clients. L’analyse de 185 entretiens approfondis a révélé trois principaux cadres discursifs que les travailleurs utilisent pour justifier la fourniture de ressources personnelles. Grâce à ces cadres, les pratiques informelles deviennent invisibles en tant que travail à plusieurs niveaux – pour soi-même, pour l’organisation et pour la société. Tout comme le travail invisible dans le ménage, son invisibilité sur le lieu de travail constitue une force principale dans la reproduction des organisations de services sociaux sexuées.
Keywords: approches et analyses; asie; discipline; inégalités; israël; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible; travail social; éthnographie institutionnelle

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

‘Where all my bad girls at?’: cosmopolitan femininity through racialised appropriations in K-pop - Garza, Joyhanna Yoo (Gender and Language, 2021)
This article examines the polyvalence of racial(ised) representations in K-pop performances. The analysis of K-pop star CL’s (2013) song and video ‘Nappeun gijibae’ (‘The bad girl’) demonstrates how the artist projects an assertive femininity by embodying and localising the Bad Bitch: a sexually agentive figure of womanhood from US hip hop. CL’s use of African American English and conventionalised hip hop tropes helps resignify gijibae, a pejorative Korean term for women. By shifting between decontextualised styles invoking a different time and place, CL is able to build a kind of chronotopic capital that transforms fragmented styles into an empowered cosmopolitan femininity. However, although CL’s performance challenges Korean gendered norms in its use of local linguistic resources, her selective appropriations of US Black and Chicanx cultural signifiers reproduce narrow images of racialised femininities and reify a hierarchy of valuation along lines of gender and race.
Keywords: 2000 à aujourd'hui; K-pop; approches et analyses; appropriation culturelle; asie; chronotope; corps; corée du sud; cours; discipline; féminisme pop; lin2685; linguistique; performance de genre; premier cycle; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques

Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Number: 2
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Enjeux politiques de la représentation visuelle coloniale en contexte de crises politiques : le cas de la photographie britannique en Inde (1857-1878) - Bernet, Myriam Maeva (Université du Québec à Montréal, 2021)
Dans le cadre de ce mémoire, j’analyse certains enjeux politiques de la représentation visuelle coloniale avant et pendant l’avènement du Raj britannique en Inde (1858-1947) période durant laquelle les possessions de la Compagnie des Indes orientales (East India Company) sont transférées à la Couronne britannique. Pour ce faire, et en m’appuyant sur les études postcoloniales et visuelles, deux périodes couvertes par deux photographes britanniques sont sélectionnées car elles renvoient à des crises politiques majeures de l’histoire de la colonisation anglaise : la première guerre d’indépendance (1857-1859) photographiée par Felice Beato et la famine de Madras (1876-1878) photographiée par Willoughby Wallace Hooper. À travers une sélection de leurs photographies, j’interroge le rôle de la production visuelle coloniale dans un contexte de crise politique, tout en prenant en compte que la pratique photographique traduisait à l’époque majoritairement un regard impérial, blanc, et masculin. L’étude du lien entre photographie et violence coloniale permet alors de démontrer que l’appareil photo est utilisé au 19ème siècle en Inde par les Britanniques comme technologie au service du pouvoir pour catégoriser, altériser (fabriquer des « Autres ») et punir les communautés colonisées, d’abord dans le but de « prouver » la supériorité militaire britannique puis sous prétexte de discours « civilisationnels ». _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : photographie coloniale, études postcoloniales, pouvoir, crise politique, études visuelles, regard colonial, colonisation britannique.
Keywords: 1800-1899; IREF; approches et analyses; asie; colonisation britannique; discipline; féminisme décolonial; inde; inégalités; mémoires/thèses; photographie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions

Paid and unpaid work during the Covid-19 pandemic: A study of the gendered division of domestic responsibilities during lockdown - Borah Hazarika, Obja; Das, Sarmistha (Journal of Gender Studies, 2021)
The Covid-19 pandemic and the strategies implemented to deal with it have had economic and societal repercussions all over the world. In India, a nationwide lockdown was initiated on 25 March 2020 which continued in a diluted form as we were conducting the interviews for the paper in July 2020. The lockdown brought activities outside the home to a standstill and people were expected to stay indoors in order to ensure social distancing and break the chain of infection. The lockdown sparked its own problems and triggered discussions on issues including economic hardship and domestic violence. The question of how domestic responsibilities are shared among adults in families has also come to the forefront of debate. As hired part-time help was discontinued under lockdown, parents who had hitherto outsourced childcare and housework were suddenly left to fend for themselves. This article attempts to explore the manner in which such unpaid domestic responsibilities, especially childcare, were shared between parents in middle-class homes. The gendered nature of this division of housework and care work, and its varied implications on the paid work and careers of mothers and fathers, is the focus of inquiry. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; conciliation famille-travail; confinement; covid-19; discipline; division sexuelle du travail; famille; inde; pandémie; projet charge mentale; périodes historiques; régions géographiques; science politique; science politique et droit; soins aux enfants; thématiques; travail; travail domestique

Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Sémi: roman - Shimazaki, Aki (Actes Sud, 2021)
« Après plus de quarante ans de mariage, Tetsuo et Fujiko se sont installés en maison de retraite car Fujiko, atteinte de la maladie d’Alzheimer, requiert une prise en charge particulière. Un matin, au réveil, elle ne reconnaît plus son époux. D’abord en grand désarroi, Tetsuo entreprend finalement de reconquérir celle qui le prend désormais pour un étranger auquel elle se trouve simplement fiancée. »– Site de l'éditeur
Section: 150 pages ; 19 cm.
Keywords: arts; asie; care; cours; discipline; japon; lit2815; premier cycle; roman; régions géographiques; thématiques; écriture des femmes*; études littéraires

The physical burden of water carrying and women’s psychosocial well-being: Evidence from rural nepal - Tomberge, Vica Marie J.; Bischof, Janine Stefanie; Meierhofer, Regula; Shrestha, Akina; Inauen, Jennifer (International Journal of Environmental Research and Public Health, 2021)
Dans les pays à faible revenu, de nombreuses femmes transportent de lourdes charges d'eau potable pour leur famille sur des terrains difficiles. Cela peut nuire à leur santé et à leur bien-être. La présente étude est la première à examiner la charge physique du transport de l'eau et le bien-être psychosocial des femmes, ainsi que la manière dont cette relation est modérée par les conditions environnementales et sanitaires. Des enquêteurs locaux formés ont mené des entretiens avec 1 001 femmes dans cinq communautés rurales du Népal. En outre, des mesures objectives ont été utilisées pour évaluer le poids porté et la distance par rapport à la source d'eau. La charge physique du transport de l'eau a été calculée à partir du poids, de la distance et de la fréquence des déplacements. Son association avec le bien-être psychosocial a été modélisée à l'aide d'équations d'estimation généralisées. Deux autres modèles incluaient le terrain et le prolapsus utérin comme modérateurs. La charge physique du transport de l'eau est directement liée à une détresse émotionnelle plus élevée et à une réduction du fonctionnement quotidien. Cette corrélation était exacerbée pour les femmes transportant sur un terrain vallonné par rapport à un terrain plat, et pour celles qui souffraient d'un prolapsus utérin. Nos résultats soulignent l'importance d'un accès adéquat à l'eau pour le bien-être psychosocial des femmes, en particulier pour les populations vulnérables telles que les femmes en mauvaise santé (par exemple, prolapsus utérin) ou celles vivant dans des terrains vallonnés. Les résultats soulignent en outre l'interdépendance de l'Objectif de développement durable (ODD) 6 : accès à l'eau, de l'ODD 3 : santé et bien-être et de l'ODD 5 : égalité des sexes.
Keywords: 2000 à aujourd'hui; asie; bien-être psychosocial; environnement; histoire et politique; népal; projet charge mentale; périodes historiques; régions géographiques; santé; santé des femmes*; thématiques; transport de l'eau potable; travail; travail reproductif

‘Passionate aesthetics’: T-P gender practices and discourses, and the hierarchies within lesbian (lala) communities in contemporary mainland China - Wang, Yiran (Journal of Gender Studies, 2021)
En tant que couple masculin-féminin comparable aux genres lesbiens butch-femme dans les sociétés euro-américaines, les rôles de genre TP constituent des éléments vivants dans la sous-culture lesbienne, ou lala , de la Chine continentale contemporaine. Sur la base d'une étude ethnographique menée au milieu des années 2010 à Shanghai et dans la province du Yunnan, en Chine, et en appliquant le cadre théorique de « l'esthétique passionnée », j'étudie dans cet article les discours et les pratiques pertinents pour les genres TP . J’analyse comment les hiérarchies ont été (re)produites au sein des communautés lala et comment, dans ces processus, les compréhensions (hétéro)normatives du genre et de la sexualité sont devenues à la fois sources de connaissances et objets de critique. Je soutiens que des esthétiques passionnées multiples et concurrentes, y compris la forme dominante d'hétéronormativité en Chine et les connaissances mondialisées, voire occidentales, sur le genre et la sexualité, ont entraîné trois grands types de hiérarchie parmi les lalas : des hiérarchies entre les catégories TP , qui sont paradoxalement définies par la notion de « pureté » ; les hiérarchies dans les discours féministes et activistes LGBTQ, qui banalisent, voire font taire, les incarnations quotidiennes du TP ; et les hiérarchies entre masculinité et féminité, qui encouragent diverses pratiques de masculinité féminine tout en valorisant la masculinité plutôt que la féminité.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; asie; chine; discipline; genre; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions

Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

S’approprier son genre entre pathologie et résistance. La transidentité après la Révolution islamique en Iran - Azadi, Bahar (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2020)
https://journals.openedition.org/cedref/1361
Keywords: asie; corps; cours; fem3400; identités LGBTQIA2+; iran; islam; personnes trans*; premier cycle; ressource en ligne; régions géographiques; thématiques

Queer China: Lesbian and gay literature and visual culture under postsocialism - Bao, Hongwei (Routledge, Taylor & Francis Group, 2020)
Ce livre analyse la production culturelle queer dans la Chine contemporaine pour cartographier les vastes transformations sociales en matière de genre, de sexualité et de désir. Il examine la littérature queer et les cultures visuelles de l'ère post-Mao et postsocialiste de la Chine pour montrer comment ces diverses formes et pratiques culturelles fonctionnent non seulement comme des formes d'activisme social spécifiques au contexte et culturellement sensibles, mais produisent également des types distincts de subjectivités de genre et sexuelles propres à Les conditions postsocialistes de la Chine. De la poésie à l'art du découpage de papier, de la « littérature camarade/gay » aux fanfictions amoureuses entre filles, des films lesbiens aux documentaires activistes, et d'un spectacle de dragsters à Shanghai à une représentation publique d'un mariage homosexuel à Pékin, le livre révèle une Chine queer dans toute sa complexité idéologique et son énergie créatrice. Riche empiriquement et méthodologiquement éclectique, Queer China tisse habilement la recherche historique et archivistique, l'analyse textuelle et discursive, ainsi que les entretiens et l'ethnographie. Innovant et mettant en avant une perspective non occidentale, ce travail transdisciplinaire contribue à de multiples domaines académiques, notamment les études littéraires et culturelles, les études sur les médias et la communication, les études cinématographiques et cinématographiques, l'art contemporain, les études de théâtre et de performance, les études de genre et de sexualité. , études Chine/Asie et pays du Sud, histoire culturelle et géographie culturelle, théorie politique et étude des mouvements sociaux.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; chine; cinéma; communication; discipline; queer; régions géographiques

Voix et travail des femmes dans les développements touristiques à Hampi - Biddle Bocan, Charlotte (Université du Québec à Montréal, 2020)
Cette recherche partira des points de vue des femmes qui travaillent dans les infrastructures touristiques de Hampi pour comprendre les développements touristiques dans cette région. À la lumière des propos énoncés par les personnes participantes à une recherche terrain, nous analyserons les enjeux politiques et sociaux provoqués par ces développements touristiques. Cette recherche a donc trois objectifs (1) mettre de l’avant les points de vue de celles, ceux qui ne sont pas entendues dans un discours dominant sur les développements touristiques (2) de comprendre ces développements touristiques à partir du point de vue de celles, ceux qui les vivent au quotidien, qui travaillent au sein de ces infrastructures touristiques et, partant de leurs voix (3) démontrer les implications sociales et politiques des restructurations suscitées par ces développements touristiques en remettant en question la littérature néolibérale et hégémonique sur les développements touristiques. Cette recherche répond à la question suivante : comment les développements touristiques à Hampi sont expliqués, organisés et revendiqués par les populations de basses castes et classes qui travaillent dans les infrastructures touristiques du village ? Nous verrons que les femmes considèrent le tourisme comme une opportunité afin de mieux répondre à leurs besoins et à ceux de leur communauté, toutefois l’importance grandissante que prendra le tourisme dans le village entrainera l’implication d’acteurs urbains et supranationaux qui déstabilisent l’organisation du travail des femmes et de leurs communautés entrainant tranquillement leur exclusion du village. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : tourisme, néolibéralisme, travail des femmes, capitalisme, développement, Inde
Keywords: IREF; asie; discipline; inde; mémoires/thèses; néolibéralisme; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques; tourisme; travail; travail des femmes*

The missing doctors — An analysis of educated women and female domesticity in Pakistan - Mohsin, Mariam; Syed, Jawad (Gender, Work and Organization, 2020)
While the percentage of female students in medical schools in Pakistan is as high as 80–85 per cent, the percentage of female doctors in the medical workforce remains below 50 per cent. Our findings draw on in-depth interviews with 31 female doctors to show that the reasons behind the gap between female medical students and female medical professionals are multifold and multilayered, ranging from individual reasons to organizational and sociocultural reasons. We use an adapted version of the relational framework developed by Syed and Özbilgin in 2009 to offer a contextual and multilevel understanding of female domesticity in Pakistan. The study suggests that the problem of female doctors dropping out of the medical workforce is a reflection of the interplay of social, organizational and individual factors, which are tied together by social norms. Practical implications suggest that making hospitals and health organizations more inclusive of women and their needs could be a starting point for policymakers to address the gender gap in the medical profession. © 2020 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; asie; conciliation famille-travail; famille; femmes* médecins; maternité; pakistan; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Benefits and constraints of the agricultural land acquisition for urbanization for household gender equality in affected rural communes: A case study in Huong Thuy Town, Thua Thien Hue Province, Vietnam - Thi, Nhung Pham; Kappas, Martin; Wyss, Daniel (Land, 2020)
Le gouvernement vietnamien a mis en œuvre l'acquisition de terres agricoles pour l'urbanisation (ALAFU) depuis 2010, ce qui a provoqué un niveau élevé de transition socio-économique dans le pays. Dans cet article, nous avons appliqué l'approche genre et développement pour découvrir comment l'ALAFU a influencé l'égalité des sexes au sein des ménages dans les zones touchées de la province de Thua Thien Hue, au Vietnam. Les données de cet article ont été principalement collectées à partir de deux enquêtes auprès de groupes de ménages, de quatre discussions de groupe et de six entretiens avec des informateurs clés. Le groupe 1 couvre 50 ménages affectés dont les terres agricoles ont été acquises pour l'urbanisation, tandis que le groupe 2 se compose de 50 ménages dont les terres agricoles n'ont pas été confisquées. Les résultats révèlent que l'ALAFU a conduit à un accès réduit aux terres agricoles pour le groupe 1, mais a contribué à une augmentation du statut économique des femmes des deux groupes en créant des opportunités d'emploi non agricoles avec un bon revenu. Cependant, la plupart de leurs nouveaux emplois sont encore informels, comportent des risques potentiels et la charge de travail de soins non rémunérés est lourde. De plus, bien que le taux de participation des femmes à la prise de décision au sein du ménage ait augmenté, la qualité de la participation est limitée. Leur participation aux activités sociales et aux cours de formation professionnelle s’est améliorée de manière insignifiante. Par conséquent, si le Gouvernement continue de promouvoir l’ALAFU, il devra prendre en compte les inégalités structurelles entre les sexes pour atteindre ses objectifs de développement durable.
Number: 8
Keywords: 2000 à aujourd'hui; 2010-2019; asie; care; participation citoyenne des femmes; projet charge mentale; périodes historiques; régions géographiques; terres agricoles; thématiques; travail; travail du care; urbanisation; vietnam

Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Number: 5 Place: Birmingham Publisher: Emerald Group Publishing Limited
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

Work-family balance and the subjective well-being of rural women in Sichuan, China - Yue Shui; Xu, Dingde; Liu, Yi; Liu, Shaoquan (BMC Women's Health, 2020)
Background Due to the great burden of family and the conflicts among family, society and career roles resulting from migrant working, rural women suffer more conflicts between work and family and need more social attention. Previous studies of the conflicts between family and work mainly focus on the group of career women, and there is a lack of the research on the conflicts between work and family of rural women, which needs to be systematically and further studied.Methods This study used a sample survey of 380 rural women in rural areas of Sichuan Province to measure rural women’s cognition of work-family, coordination and handling of conflicts, post-conflict choices, and subjective well-being; the study constructs an ordered multi-class logistic regression model to explore the impact of work-family conflict on the subjective well-being of rural women in rural regions.Results The study result shows that: (1) The level of subjective well-being of rural women is generally high, and 70% of women feel satisfied or very satisfied. (2) The factor which impacts the subjective well-being among rural women most is work-interfering-with-family conflict, followed by work-family balance and confidence in conflict coordination.Conclusion This study can enhance our understanding of rural women in rural areas, and provide a reference for formulating policies to improve people’s life satisfaction.
Keywords: 2000 à aujourd'hui; 2010-2019; asie; bien-être psychosocial; chine; conciliation famille-travail; famille; femmes rurales; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
https://www.feministeconomics.net
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

Intégrer la dimension de genre dans le développement de clusters - Département du commerce, des investissements et de l'innovation; Organisation des Nations Unies pour le développement industriel (ONUDI, 2019)
Keywords: EDI; OFDIG; afrique; approches et analyses; asie; autodétermination; discipline; entrepreneuriat; genre; identités LGBTQIA2+; international; rapports sociaux de sexe; régions géographiques; sciences de la gestion; thématiques; économie; égalité des sexes

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Disponible en ligne à https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/racializing-heterosexuality-nonnormativity-and-east-asian-characters-in-james-bond-films/52C50BE7F19552D50389CDED9913BCE3
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Paid–unpaid work continuum of women: Home-based workers and self-employed women in the national capital region - Sengupta, Sudeshna (Indian Journal of Labour Economics, 2019)
Women’s work is a continuum that intersperses productive work with reproductive work, unpaid work with paid work and all kinds of activities with leisure and self-care. She plans, manages and implements her work at home, often being responsible for all the three domains. Women from working-class families may seem to be making a “choice” in deciding the continuum, and delving deep, we find that it is more often a “coping mechanism” in “managing poverty” of all forms—income, time and opportunity. This paper explores how women’s organisation of work is influenced by the interplay of three institutions—State, market and family, and how gendered division of work is reproduced in the process. © 2019, Indian Society of Labour Economics.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; division sexuelle du travail; famille; inde; pauvreté; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail de reproduction; travail gratuit; travail rémunéré; travailleuses à domicile

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Santé sexuelle et autonomie reproductive : étude qualitative sur les expériences et représentations des femmes universitaires de Mumbai, Inde - Beauchemin-Roy, Sarah (Université du Québec à Montréal, 2018)
Cette recherche vise à explorer les expériences et représentations des femmes indiennes universitaires quant à leur santé sexuelle et reproductive. Plus précisément, il s'agit d'explorer les normes sociales et les enjeux associés à la décision d'avoir une vie sexuelle active ; de documenter les expériences et perceptions des femmes quant à leurs connaissances et à l'utilisation des méthodes de contraception ; et de décrire leur pouvoir de décision et de contrôle sur leur stratégie contraceptive. Pour y arriver, une recherche qualitative exploratoire a été menée de septembre à novembre 2016 à Mumbai, en Inde. Les 10 participantes sont des étudiantes au collège ou à l'université, sexuellement actives dans les douze derniers mois, âgées de 20 à 25 ans, qui ont pris part à une entrevue semi-dirigée de 60 minutes. Les résultats indiquent que les jeunes femmes universitaires font face à de nombreux obstacles à l'atteinte d'une autonomie reproductive et donc, d'une santé sexuelle et reproductive optimale. Tout d'abord, les normes patriarcales établies par les structures sociales et culturelles influencent les représentations de la sexualité féminine dans la société. Ensuite, quant aux expériences sexuelles des participantes, elles sont modulées par la famille et le réseau des pairs ; le premier étant un obstacle et le deuxième étant un facilitateur à la transgression des normes et des attentes sociales envers les femmes. Enfin, plusieurs facteurs interpersonnels et individuels élaborés dans ce mémoire jouent un rôle déterminant dans l'atteinte d'une autonomie reproductive. Pour conclure, il sera pertinent de se pencher sur les limites de cette recherche ainsi que sur des recommandations. Or, considérant que des changements majeurs sont nécessaires à plusieurs niveaux, des recommandations globales seront proposées. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : autonomie reproductive, santé sexuelle et reproductive, justice reproductive, méthodes contraceptives, étudiantes collégiales et universitaires, Mumbai, Inde
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; asie; contraception; discipline; inde; justice reproductive; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; étudiantes indiennes

Établissement et stratégies d'intégration des immigrants syriens à Montréal, 1890-1945 - Djahnine, Yasmine (Université du Québec à Montréal, 2018)
Tout au long de leur développement, le Canada et le Québec ont connu de nombreuses vagues d'immigration constituées principalement de personnes en provenance d'Europe. Toutefois, à partir de la fin du XIXe siècle, on voit apparaître des groupes de personnes en provenance de l'Asie et du Proche-Orient. À travers notre recherche, nous avons exploré l'immigration syrienne qui a eu lieu à Montréal au tournant du XXe siècle. Dans les quelques travaux qui ont été réalisés sur la communauté syrienne de Montréal, l'ethnie est souvent l'unique grille d'analyse. La communauté n'est étudiée qu'à travers la religion, le lieu d'origine et la transmission de l'héritage culturel et traditionnel. Afin d'enrichir le corpus d'études existant sur cette communauté, nous étudions l'articulation des stratégies d'intégration des membres de la première génération d'immigrants syriens à Montréal entre 1890 et 1945. Les immigrantes et les immigrants sont des acteurs qui traversent les frontières, qui mettent en place des stratégies tout au long du processus migratoire et qui construisent divers réseaux. Ils ne sont pas uniquement mus par le marché du travail ou par les traditions culturelles; ils développent des stratégies dans leur pays d'origine et tout au long de leur établissement dans la société d'accueil. Ainsi, dans un premier temps, nous avons examiné la société et le milieu duquel ils proviennent afin de circonscrire les facteurs qui les ont amenés à amorcer leurs plans migratoires. Dans un deuxième temps, grâce aux recensements canadiens et aux annuaires Lovell, il a été possible de dresser un portrait de l'évolution de l'installation des Syriens à Montréal. Dans un dernier temps, cette recherche révèle que les stratégies d'intégration dans le pays hôte s'articulent principalement autour de deux axes. D'une part, c'est autour des multiples réseaux sociaux mis sur pied par les membres de la communauté syrienne; de l'autre, par la mobilisation et la résistance politiques qui ont ponctué leur histoire au fil des décennies. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Histoire, Montréal, Immigration, Syriens, Stratégie, XXe siècle, Régulation, Réseaux.
Keywords: 1900-1999; IREF; amériques; asie; discipline; histoire; immigration; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; syrie

Rencontres radicales : pour des dialogues féministes décoloniaux - Altamimi, Manal; Dor, Tal; Guénif Souilamas, Nacira (Cambourakis, 2018)
Comment tenter de trans/former la conscience de personnes engagées dans des situations de conflit, des tensions sociales et raciales et en quête de changements politiques significatifs ? Trois types de textes se font ici écho : six auteur·e·s analysent les « rencontres radicales » organisées entre Palestinien·ne·s et Israélien·ne·s ; bell hooks écrit sur l’éducation à/par l’émancipation dans le contexte des discriminations raciales aux États-Unis ; enfin, trois participant·e·s à des groupes de rencontre en Kanaky/Nouvelle-Calédonie nous proposent un troisième point d’ancrage en cette année de référendum d’autodétermination. Un ouvrage collectif qui vise à donner voix ensemble aux militant·e·s et aux théories, engageant un dialogue qui offre un répertoire d’actions et de réflexions puissant et décapant au confluent du féminisme, de l’analyse de la colonialité et d’une radicalité revendiquée. Essais de bell hooks, Rabah Halabi, Michal Zak, Nava Sonnenschein, Ramzi Suleiman, Ahmad Hijazi, Tal Dor, Angélina Perrochaud, Pascal Hébert, Pierre Wélépa et Nassira Hedjerassi.
Postface de Nassira Hedjerassi
Keywords: afrique; amériques; approches et analyses; asie; cours; fem3100; féminisme décolonial; histoire et politique; israël; militance; nouvelle calédonie; océanie; palestine; premier cycle; régions géographiques; thématiques; états-unis

The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

Féminicides en Inde : un continuum de violence contre les femmes - Messier, Geneviève (Université du Québec à Montréal, 2018)
Ce travail de recherche dirigé s'intéresse aux différentes manifestations de la violence faite aux femmes en Inde, particulièrement à la violence mortelle envers les femmes. Il s'agit de démontrer l'existence d'éléments de continuité entre trois types de violence différents, c'est-à-dire les foeticides, ou avortements sélectifs des foetus de sexe féminin, les violences sexuelles et mortelles contre les femmes dans l'espace public ainsi que les violences contre les femmes dans les zones de conflit du territoire indien. L'analyse de chacune de ces manifestations de violence a été faite par le biais d'éléments de définition du concept de féminicide. Trois aspects de la définition de féminicide présentée dans ce travail ont été systématiquement analysés pour les trois types de violence identifiés. Chacun de ces types de violence se déroule dans le cadre de rapports sociaux de sexe inégaux, dans une situation d'impunité créée par le gouvernement indien et le concept d'intersectionnalité a permis de démontrer que les éléments identitaires des femmes indiennes autres que le genre jouent un rôle prépondérant pour expliquer la violence dont elles sont victimes. Cette analyse nous a permis de démontrer l'existence d'un continuum de la violence contre les femmes en Inde. Ce continuum s'étend de la sphère privée à la sphère publique et concerne le niveau local tout comme l'arène internationale. De plus, ce travail a aussi permis de démontrer la pertinence du concept de féminicide à l'extérieur du contexte latinoaméricain dont il est issu. Les résultats de ce travail se trouvent limités par le fait que seulement trois types de violence ont pu être analysés et que certains types de violences spécifiques au contexte indien, comme les épouses brûlées vives (bride burning) et les meurtres pour la dot, n'ont pas pu être intégrés à l'analyse. ___________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : féminicide, continuum de la violence, Inde, violence faite aux femmes
Keywords: IREF; approches et analyses; asie; discipline; inde; mémoires/thèses; patriarcat; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; violences

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Justice is indivisible: Palestine as a feminist issue - Elia, Nada (Decolonization: Indigeneity, Education & Society, 2017)
⠀⠀⠀⠀⠀⠀⠀⠀⠀
Number: 1
Keywords: approches et analyses; asie; cours; féminisme arabe; féminisme décolonial; histoire et politique; palestine; pol4212; premier cycle; ressource en ligne; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

Black history month: Diversity and the British female suffrage movement - Mukherje, Sumita (The Fawcett Society, 2017)
The fight for the female vote was not solely a British, or a ‘white’ concern, writes historian Sumita Mukherjee.
https://www.fawcettsociety.org.uk/blog/diversity-british-female-suffrage-movement
Keywords: approches et analyses; asie; cours; droits des femmes*; europe; fem1000; féminisme décolonial; inde; mouvements des femmes*; premier cycle; royaume-uni; régions géographiques; suffragettes; thématiques

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Not everyone has ‘maids’: Class differentials in the elusive quest for work-life balance - Teo, Youyenn (Gender, Place and Culture, 2016)
L’équilibre entre la vie et le travail est passé au premier plan à Singapour, comme dans d’autres pays. Les débats se concentrent sur les charges épargnées entre les générations. Menos atención se ha prestado a cómo influyen los asuntos de clase en el resultado para las mujeres. Dans cet article, il est dit que le régime de travail et de soins à Singapour génère des conséquences désagréables entre les femmes dans leur classe. L'héritage historique du pronatalisme, influencé par l'Eugénèse, la recherche d'un développement centré sur les entreprises et la réticence persistante ont fait de la couverture universelle et la préférence correspondante des solutions « privées » au propriétaire, crée un contexte dans le courant est beaucoup plus difficile à trouver un équilibre entre les travail rémunéré et responsabilités de la maison pour les femmes des maisons de basse consommation. L'individualisation et la commercialisation des nécessités de la maison, à Singapour et dans d'autres endroits en général, tiennent compte des circonstances, des nécessités et du bien-être des femmes dans une situation de classe inférieure et socava la valeur de la maison et le travail du personnel.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; capitalisme; conciliation famille-travail; famille; pauvreté des femmes; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; singapour; systèmes d'oppressions; thématiques; travail; travail invisible

CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Témoin de la nuit: roman - Desai, Kishwar; Dauvergne, Benoîte (Éd. de l'Aube, 2013)
Simran Singh est chargée d'une affaire délicate : une adolescente est retrouvée dans la luxueuse maison familiale, bâillonnée et brûlée après avoir été violée. Autour d'elle, treize cadavres empoisonnés. Bientôt, la police soupçonne la jeune fille ! À charge pour Simran de découvrir la vérité, dans une société où naître fille peut s'avérer dangereux…
Section: 1 vol. (228 p.) : couv. ill. ; 22 cm.
Keywords: 2000 à aujourd'hui; Roman policier; arts; asie; cours; discipline; inde; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Conférence: «Retour du sacré et politique des différences culturelles» (2012)
Conférence de Haideh Moghissi présentée en anglais le 3 octobre 2012 à l’Institut de recherches et d'études féministes. Haideh Moghissi est professeure de sociologie et d'études des femmes à l'Université York (Toronto). Elle a été fondatrice de l'Union nationale des femmes iraniennes et membre de ses premiers comités exécutif et de rédaction, avant de quitter l'Iran en 1984.
Keywords: approches et analyses; asie; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; mouvements des femmes*; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques

N'est pas mère qui veut. Le paradoxe de l'adoption internationale - Reysoo, Fenneke; Bos, Pien (Nouvelles Questions Féministes, 2011)
La circulation d’enfants entre une mère biologique et des parents adoptifs soulève des questions sur la pluralité des systèmes de genre et les inégalités sociales méconnues jusqu’ici. Nous menons une réflexion sur la situation paradoxale qui lie deux systèmes de genre : en Inde, il enjoint des femmes non mariées à renoncer à vivre leur maternité et, en Occident, il pousse les femmes avec un emploi à retarder la conception de leur premier enfant, ce qui augmente le risque de fécondabilité réduite et ouvre la voie au recours à l’adoption. Notre étude, au Tamil Nadu (Inde), parmi les mères biologiques montre que la production d’enfants adoptables relève de rapports de pouvoir très complexes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; corps; cours; discipline; inde; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Ethnocentrisme occidental et perceptions du harem - Ahmed, Leila (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2010)
En 1980, lors de la conférence de la National Women’s Studies Association qui s’est tenue à Bloomington, Indiana, j’ai assisté à une présentation sur « Les femmes dans l’islam » au cours de laquelle je suis intervenue vivement, depuis ma place dans le public, car les intervenantes invitées, trois femmes arabes, présentaient, selon moi un tableau idéalisé de la situation des femmes dans l’islam. Les sociétés islamiques se distinguaient peut-être même plutôt – c’est en tout cas ce que je pensais à l’époque – par le fait qu’elles plaçaient sans équivoque les femmes sous le contrôle des hommes et par le fait qu’elles accordaient aux hommes, de façon tout aussi explicite, le droit à une sexualité et le droit d’exploiter les femmes. Comme le soutenaient les intervenantes, à son avènement l’islam avait apporté un certain nombre de progrès positifs pour les femmes en Arabie. Il avait également accordé certains droits aux femmes tels que le droit à la propriété (qui, en Occident, ne fut accordé aux femmes qu’au dix-neuvième siècle et qui n’est d’ailleurs toujours pas accordé aux femmes selon, parexemple, la loi rabbinique, tout comme le droit de témoigner). Et on ne pouvait certainement pas dire que l’islam était plus malveillant à l’égard des femmes que les deux autres religions monothéistes. Cependant, il me semblait que cela ne justifiait en rien le fait de minimiser la position d’approbation flagrante qui est celle de l’islam en ce qui concerne la supériorité des hommes et le contrôle exercé par ces derniers sur les femmes. Ni d’ailleurs le fait d’occulter les difficultés rencontrées par les femmes, en particulier en ce qui concerne les lois sur le mariage, le divorce et la garde des enfants. Cet article est la traduction de : « Western Ethocentrism and Perceptions of the Harem », Feminist Studies, vol. 8, n°3, autumn 1985, p. 521-534. Cet article a été écrit en 1982 donc avant la disparition de l’Union Soviétique qui date de 1992.
Première publication 1982
Keywords: approches et analyses; asie; cours; discipline; droits des femmes*; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; occident; orient; premier cycle; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sciences juridiques; sciences sociales; sociologie; stéréotypes; thématiques; voiles islamiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Entre silence et fracas : émergence et affirmation des luttes féministes dans les communautés juives orthodoxes en Israël (1970-2009) - Pouzol, Valérie (Le mouvement social, 2010)
Né au lendemain de la guerre du Yom Kippour en 1973, le mouvement féministe israélien s'est concentré sur la déconstruction des mythes nationaux égalitaires ainsi que sur la charité envers les femmes dans le besoin dans une société militarisée. Dans cette lutte, le mouvement, majoritairement laïc et fortement divisé entre diverses ethnies, a peu orienté son énergie vers les femmes orthodoxes. L'activisme des femmes juives orthodoxes, cependant, est une tradition forte et séculaire. Cet article présente une analyse sociologique du militantisme de ces femmes orthodoxes en retraçant l'itinéraire de leurs luttes dans la société israélienne. Ces luttes ne se limitent pas à l'orientation politique traditionnelle du monde religieux israélien, souvent en faveur d'un « Grand Israël ». En effet, dès le début du mouvement dans les années 1990, Alors que les nationalistes religieux ont durci leur position et que les colons ont dérivé vers la violence, les femmes orthodoxes ont organisé un effort alternatif pour faire le point sur la radicalisation des forces religieuses dans le pays et mettre en avant la difficulté pour elles de prendre position et de militer contre la guerre. En 1998, elles vont encore plus loin en créant un groupe contre la guerre appelé Women for the Sanctity of Life. femmes, ainsi que les dangers auxquels elles sont confrontées en raison de leur position dans un monde orthodoxe qui résiste au changement et qui place la pureté de la femme au centre de son appareil idéologique
Keywords: asie; cours; discipline; fem1000; israël; militance; mouvements féministes; premier cycle; religion; régions géographiques; résistance; sciences humaines; sociologie; thématiques

Les monologues voilés (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Place: Paris Publication Title: Scènes & Cies
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte

Being "Good" or Being "Popular": Gender and Ethnic Identity Negotiations of Chinese Immigrant Adolescents - Baolian Qin, Desiree (Journal of Adolescent Research, 2009)
Keywords: 2000 à aujourd'hui; 2000-2009; adolescence; amériques; approches et analyses; asie; chine; corps; cours; discipline; identité des femmes*; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexualité; thématiques; travail; états-unis

Indian tango - Devi, Ananda (Gallimard, 2009)
Indian Tango se déroule en 2004 à Delhi sur fond de pluies de mousson. Cela se produit lors des élections générales qui verraient Sonia Gandhi diriger brièvement un gouvernement de coalition. Un écrivain en visite devient obsédé par Subhadra, une femme aperçue dans la rue, et une relation non conventionnelle se développe. Cette histoire explore le coût de la poursuite de la passion et du désir dans une société dynamique mais profondément conservatrice. Il s'agit d'une méditation émouvante sur les limites que les conventions ont imposées à la vie des femmes et sur la manière dont elles les surmontent. L'œuvre d'Ananda Devi est à la fois tragique et poétique. Hantée par les questions d'exclusion, d'altérité, de déviance et de souffrance, elle dénonce le climat étouffant d'une société... elle s'oppose à toute forme de rejet et propose un véritable engagement... pour la reconnaissance de l'altérité. – Véronique Bragard
Keywords: 2000 à aujourd'hui; 2000-2009; asie; corps; inde; périodes historiques; régions géographiques; sexualité; thématiques

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Les relations entre la participation aux programmes de microfinance et les processus d'empowerment des femmes - Langevin, Marie (Université Laval, 2009)
Ce mémoire analyse les relations entre la participation aux programmes de microfinance et les processus d'empowerment des femmes. Au moyen d'une étude de cas à portée comparative de deux institutions de microfinance asiatiques, la Grameen Bank du Bangladesh et Self Employed Women's Association (SEWA) en Inde, j'examine, en fonction des données secondaires déjà publiées, dans quelle mesure ces institutions ont un effet sur les processus d'empowerment des participantes. J'analyse précisément les effets en regard de six dimensions de l'empowerment (économique, socioculturelle, familiale/interpersonnelle, juridique, politique et psychologique) se manifestant au niveau personnel ou du ménage et au niveau de la communauté. Enfin, j'étudie dans quelle mesure, ces effets sont modulés par le contexte d'action des institutions et par le type d'approche qui encadre la mise en oeuvre de leurs programmes de microfinance.
Keywords: OFDIG; asie; bangladesh; discipline; femmes*; inde; microfinance; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques; travail

Looking for Asian butch-dykes: Exploring filmic representations of east Asian butch-dykes in Donna Lee's Enter the mullet - Lin, Hui-Ling (Journal of Lesbian Studies, 2009)
Asian butch-dykes have been overlooked in analyses of Chinese cinema, studies that often concentrate on “feminized” transgender roles. This article examines cinematic representations of Asian butch-dykes through film analysis of Enter the Mullet (2004), a five minute short, and in-depth interviews with the filmmaker, Donna Lee, a Chinese-Canadian in Vancouver. Lee’s film is inspired by Enter the Dragon (1973), starring Bruce Lee, the most recognized icon of Asian masculinity. Combining with the mullet hairstyle, which is often associated with White working-class, the filmmaker introduces viewers to the hybrid masculinity of Asian butch-dykes. The article argues that Asian female masculinity can be a strategic means of destabilizing the hegemony of White–male–middle-class masculinity
Number: 1
Keywords: amériques; approches et analyses; asie; canada; chine; identités LGBTQIA2+; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »– Quatrième de couverture.
Section: 144 pages ; 23 cm
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Femmes, ethnicité et religion : la communauté tamoule hindoue du Sri Lanka à Montréal - St-Germain Lefebvre, Catherine (Université du Québec à Montréal, 2008)
Convaincue que les femmes, de par leur rôle dans les rapports sociaux de sexe, ont un rôle important à jouer dans la transmission de l'identité ethnique aux jeunes générations, nous avons voulu, dans ce mémoire, mettre à jour ce phénomène tel qu'il se déploie dans la communauté tamoule du Sri Lanka immigrée à Montréal. La perspective féministe en influence la trame de fond, contribuant à orienter le choix du sujet ainsi que son traitement. Ce mémoire est le fruit d'une recherche exploratoire de type qualitatif. Il repose sur un terrain de recherche mené au temple hindou Thiru Murugan situé à Dollard-des-Ormeaux, municipalité de l'ouest de l'île de Montréal. Il a pour objectif de définir la contribution spécifique de femmes de cette communauté à la « production de l'ethnicité » tamoule, au sens entendu par la sociologue des relations ethniques, Danielle Juteau. Ce mémoire s'appuie sur un cadre théorique contribuant à jeter les bases d'une définition sociologique de l'ethnicité, où non seulement le rôle des femmes dans sa production/reproduction est mise de l'avant, mais où se dégage également l'importance de la composante religieuse dans l'affirmation ethnique, particulièrement en contexte migratoire. Cette recherche analyse d'une part la perception du rôle des femmes dans les rapports de sexe tels qu'ils se déploient dans la communauté tamoule montréalaise et telle qu'elle a été exprimée par les personnes interrogées dans le cadre de cette étude. Il s'attarde d'autre part à l'implication des femmes de cette communauté dans la transmission de la langue, de la religion et de la culture. Ce mémoire démontre que les idéaux associés à la conception de la féminité influencent à· maints égards le rôle des femmes dans les rapports sociaux de sexe à l'oeuvre dans la communauté étudiée. Ce rôle amène celles-ci à s'impliquer activement dans la transmission de leur identité ethnique auprès des générations nées au Québec. De plus, la pratique religieuse jouant un rôle important dans la formation identitaire de nos répondant(e)s, la dimension religieuse est omniprésente dans le bagage ethnique transmis par les femmes aux jeunes générations. Par leur travail actif et conscient lié à la transmission de la langue, de la culture et de la religion aux jeunes de la communauté, ces femmes participent activement à reproduire les frontières ethniques de leur communauté et contribuent, par cela, à la « production de l'ethnicité » tamoule hindoue du Sri Lanka en contexte québécois. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Femmes, Ethnicité, Religion, Transmission, Hindouisme, Tamoul, Sri Lanka.
Keywords: IREF; amériques; approches et analyses; asie; discipline; femmes* tamoules; hindouisme; montréal; mémoires/thèses; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sri lanka

South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

The nature of gender: work, gender, and environment - Nightingale, Andrea (Environment and Planning D: Society and Space, 2006)
Le genre est depuis longtemps reconnu comme important dans les questions environnementales, mais la manière de conceptualiser le lien entre genre et environnement fait l’objet de nombreux débats. Les théories féministes sur les femmes et le genre ont évolué, tout comme les conceptualisations sur le genre et l’environnement, ce qui a donné lieu à un débat clé au sein de l’écoféminisme et des littératures associées sur la question de savoir s’il existe une relation essentielle ou contingente entre les femmes et les environnements naturels. En géographie, la plupart des écologistes politiques partent du principe que le lien entre genre et environnement est une relation contingente, et étudient donc la manière dont les relations de genre sont saillantes dans la construction symbolique et matérielle des questions environnementales. Dans cet article, je cherche à m’appuyer sur ce travail et à soulever à nouveau la question de la manière dont le genre est conceptualisé par rapport à l’environnement. Je commence par passer brièvement en revue certains des travaux qui ont été réalisés sur le genre et l’environnement, puis je m’inspire du féminisme post-structural pour suggérer que le genre lui-même a été sous-théorisé dans les travaux sur l’environnement. Une fois que le genre est reconceptualisé en tant que processus, la relation dynamique entre le genre, l’environnement et d’autres aspects de la vie sociale et culturelle peut être mise en évidence. Il en ressort que les écologistes politiques doivent examiner la question du genre au-delà du foyer et de la communauté, et reconceptualiser le lien entre le genre et l’environnement. Une étude de cas sur la foresterie communautaire au Népal est utilisée pour illustrer l’importance d’interroger les processus par lesquels les relations entre les sexes deviennent saillantes et sont reproduites symboliquement et matériellement.
Keywords: approches et analyses; asie; discipline; environnement; géographie; histoire et politique; népal; politique écologique; post-structuralisme; projet charge mentale; régions géographiques; sciences humaines; sociologie; thématiques; écoféminisme

Voices of South Asian Women: Immigration and Mental Health - Ahmad, Farah; Shik, Angela; Vanza, Reena; Cheung, Angela M.; George, Usha; Stewart, Donna E. (Women & Health, 2005)
Purpose: This qualitative research aimed to elicit experiences and beliefs of recent South Asian immigrant women about their major health concerns after immigration. Methods: Four focus groups were conducted with 24 Hindi-speaking women who had lived less than five years in Canada. The audiotaped data were transcribed, translated, and analyzed by identification of themes and subcategories. Results: Mental health (MH) emerged as an overarching health concern with three major themes, i.e., appraisal of the mental burden (extent and general susceptibility), stress-inducing factors, and coping strategies. Many participants agreed that MH did not become a concern to them until after immigration. Women discussed their compromised MH using verbal and symptomatic expressions. The stress-inducing factors identified by participants included loss of social support, economic uncertainties, downward social mobility, mechanistic lifestyle, barriers in accessing health services, and climatic and food changes. Women's major coping strategies included increased efforts to socialize, use of preventative health practices and self-awareness. Conclusion: Although participant women discussed a number of ways to deal with post-immigration stressors, the women's perceived compromised mental health reflects the inadequacy of their coping strategies and the available resources. Despite access to healthcare providers, women failed to identify healthcare encounters as opportunities to seek help and discuss their mental health concerns. Health and social care programs need to actively address the compromised mental health perceived by the studied group.
Keywords: amériques; asie; asie du sud; canada; charge mentale; cours; discipline; femmes immigrantes; médecine; régions géographiques; santé; sciences; soc1061; stress post immigration; thématiques

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

La démocratie et le statut des femmes au Liban - Bdeir, Leila (Université du Québec à Montréal, 2005)
Keywords: IREF; approches et analyses; asie; discipline; femmes* politiques; liban; militance; mouvements féministes; mémoires/thèses; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Quand les femmes écrivent la guerre : transformation du genre et du monde dans Les hommes qui marchent de Malika Mokeddem et Iran, les rives du sang de Fariba Hachtroudi - Bélanger, Marie-Ève (Université du Québec à Montréal, 2005)
Keywords: 1900-1999; 1990-1999; IREF; afrique; algérie; asie; discipline; guerre; iran; mémoires/thèses; périodes historiques; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Quatre mille marches - Chen, Ying (Boréal, 2004)
« Romancière avant tout, Ying Chen a tout de même rédigé, au fil des ans, des textes dans lesquels elle tente de réfléchir simplement, modestement, en adoptant le mode de l’interrogation, du souvenir et de la lettre familière plutôt que celui de l’analyse ou de la théorie, à ce que sont pour elle - et peut-être pour ses lecteurs - la portée et la signification de son art, le sens de son itinéraire personnel de femme, d’exilée et d’écrivain, ou la place de la littérature dans le monde éclaté d’aujourd’hui. Il en résulte une série d’essais brefs, écrits dans une prose aussi sobre que directe, qui constituent d’une certaine manière l’accompagnement ou l’écho méditatif de cette parole qui se fait entendre dans ses romans et à travers la voix des personnages auxquels elle a donné vie. »
Section: 126 pages ; 22 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; asie; chine; cours; discipline; lit2815; lit3495; point de vue situé; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
https://www-cairn-info.proxy.bibliotheques.uqam.ca/revue-mouvements-2004-1-page-97.htm
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

‘Who is the Developed Woman?’: Women as a Category of Development Discourse, Kumaon, India - Klenk, Rebecca M. (Development and Change, 2004)
This article analyses gendered discourses of development in rural North India, and addresses the usefulness of recent scholarship on development as ‘discourse’ for understanding connections between development and subjectivity. This scholarship is an excellent point of departure for exploring the contradictions inherent in the institutionalization of economic development and the global reach of its discourses, but it has focused primarily upon development as discourse at official sites of deployment, while paying less attention to how specific discourses and processes of development are appropriated by those constituted as beneficiaries of development. The under-theorization of this aspect has meant that the range of processes through which development projects may encourage new subject positions are poorly understood. By investigating what some women in rural Kumaon have made of their own development, this article contributes to emerging scholarship on development and subjectivity with an ethnographic analysis of the polysemic enthusiasm for development expressed by some of its ‘beneficiaries’.
Keywords: Kumaon; anthropologie; approches et analyses; asie; cours; discipline; développement; féminisme décolonial; histoire et politique; inde; pol4022; premier cycle; relations internationales; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Mousson de femmes - Perrin, Elula (La Cerisaie, 2003)
Récit d'un amour passionné entre deux femmes en Indochine pendant la Seconde Guerre mondiale. Elula Perrin, née à Hanoi en 1929, témoigne de la terreur et des tueries perpétrées en Indochine entre 1945 et 1946.
Keywords: 1900-1999; 1940-1949; approches et analyses; asie; guerre; mémoire collective; personnes lesbiennes; périodes historiques; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; violences

Enjeux contemporains du féminisme indien - Haase-Dubosc, Danielle (Éditions de la Maison des sciences de l'homme, 2002)
Pour la première fois en français, un recueil d'essais témoigne des luttes et de la politique féministes en Inde, dans un contexte bien différent des problématiques occidentales. Inscrits dans la période contemporaine, de la turbulence des années 1960 et 1970 aux défis des années 1990, certains de ces textes ont été rédigés à chaud, d'autres sont plus rétrospectifs. Ils constituent un ensemble original à travers six grandes rubriques qui se complètent et se répondent l'une l'autre ... Tout en présentant les expériences historiques particulières qui ont nourri les théories et les pratiques du mouvement des femmes en Inde, cet ouvrage présente une approche vivante et engagée des questions actuellement en jeu pour les femmes indiennes.une vision plurielle du féminisme , dans une perspective transnationale respectueuse de l'altérité historique et culturelle
Keywords: 1900-1999; 1960-1969; 1970-1979; approches et analyses; asie; conflit; cours; cycles supérieurs; droits des femmes*; fem1000; fem7000; histoire des femmes*; histoire et politique; inde; inégalités; lit3220; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs – qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those – the vast majority – who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Doing fieldwork on women in theocratic Islamic states: A critique of the politics of empiricism - Mojab, Shahrzad (Resources for Feminist Research, 2001)
This paper examines the way some feminist advocates of cultural relativism adopt positivism and empiricism in order to discredit the radical critique of Islamization of gender relations in Iran. It argues that relativists use the positivist/empiricist cult of experience and objectivity in order to undermine the critique of policies and practices that oppress the women of Iran. The choice of a method of inquiry is not based on methodological considerations only. The researcher's political preferences, implicit or explicit, plays a significant role in the entire research process, especially in the study of sensitive issues. Although one may identify a methodological tradition with a certain brand of politics, the paper argues that methodological paradigms enter into changing relationships with structures of power.
Keywords: approches et analyses; asie; cours; discipline; discours dominant; fem1000; iran; méthodologie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; épistémologie

Le mythe de l'émancipation des femmes russes - Robinson-Chouinard, Ève (Université du Québec à Montréal, 2001)
Keywords: IREF; asie; avortement; discipline; europe; justice reproductive; mémoires/thèses; russie; régions géographiques; science politique; science politique et droit; thématiques